A Dual-Port Dual-Wideband Dual-Sense Circularly Polarized DRA With a Novel Feeding Mechanism - Li Zhang; Jian-Wei Liu; Bo Chen; Liang-Yong Yi; Dian Liu; Zi-Bin Weng; Yong-Chang Jiao (IEEE Open Journal of Antennas and Propagation)
A dual-wideband dual-sense circularly polarized (CP) dielectric resonator antenna (DRA) based on a novel feeding technique is investigated and demonstrated. The proposed antenna is composed of a cylinder DR, a ground plane with a double cross-slot and two rectangle slots, and a novel feeding structure. In the lower band, the DR is fed by two vertical metal probes, and the antenna can be fed by a novel feeding method in the upper band. Based on these feeding mechanisms, a pair of orthogonal modes can be excited in the lower band, and the slot modes can be obtained in the upper band. For demonstration, one prototype is fabricated and measured. The measured results show that the presented antenna obtains a wideband impedance bandwidth of 21.3% (2.18-2.7GHz) and 3dB axial ratio (AR) bandwidth of 13.2% (2.2-2.51GHz) in the lower band for the left-hand circular polarization (LHCP) and obtains a wideband impedance bandwidth of 19.2% (4.7-5.7GHz) and 3dB AR bandwidth of 13.0% (4.91-5.59GHz) in the upper band for the right-hand circular polarization (RHCP). Furthermore, the two bands of the proposed antenna can cover the Wi-Fi band, and the antenna has a stable gain in the band.